Potential biocontrol efficiency of Trichoderma species against oomycete pathogens - Liu, Yinglong; He, Pengbo; He, Pengfei; Munir, Shahzad; Ahmed, Ayesha; Wu, Yixin; Yang, Yuling; Lu, Junping; Wang, Jiansong; Yang, Jizhou; Pan, Xinlong; Tian, Yangyang; et al. (Frontiers in Microbiology, 2022)
Plant health is utmost important for optimal agricultural production and sustainability. Unfortunately, biotic and abiotic factors put major constraint on food safety and productivity. Plant diseases caused by oomycetes cause serious damage to various crops. Moreover, injudicious use of chemical pesticides poses threats related to pesticide resistance development in pathogens and environmental pollution. Biocontrol offers an effective solution for disease control, however research on biocontrol of oomycete-related disease is scarce. Thus, present study undertakes the screening of biocontrol resources for effective management of oomycete related plant diseases. In this regard, 86 isolates of Trichoderma spp. were assessed against Phytophthora nicotianae, P. capsici, Pythium vexans, Py. ultimum and Py. dissotocum through dual culture assay. Furthermore, antagonistic effect of selected isolates was studied against tobacco black shank disease and damping-off of cucumber seedlings in the greenhouse. The relative control effect of the three antagonistic Trichoderma strains AR-4, Tv-1 and ST4-1 on tobacco black shank was more than 60%, which was not significantly different from 6.88 g·l−1 Fluopicolide·Propamocarb. Whereas, the relative control effect of Trichoderma AR-4 and ST4-1 on damping-off of cucumber seedlings was 80.33% and 82.67% respectively, which were significantly higher than Trichoderma Tv-1 (35.49%) and Fluopicolide·Propamocarb (47.82%). According to the morphological and molecular characterization, the fungal strains AR-4, Tv-1 and ST4-1 were identified as Trichoderma koningiopsis, T. asperellum and T. gamsii, respectively. In conclusion, the strains exhibited strong antagonistic effect against oomycete pathogens and can be integrated in disease management strategies.